ApoE and ApoE Nascent-Like HDL Particles at Model Cellular Membranes: Effect of Protein Isoform and Membrane Composition - Waldie, Sarah; Sebastiani, Federica; Moulin, Martine; Del Giudice, Rita; Paracini, Nicolò; Roosen-Runge, Felix; Gerelli, Yuri; Prevost, Sylvain; Voss, John C.; Darwish, Tamim A.; Yepuri, Nageshwar; Pichler, Harald; et al. (Frontiers in Chemistry, 2021)
Apolipoprotein E (ApoE), an important mediator of lipid transportation in plasma and the nervous system, plays a large role in diseases such as atherosclerosis and Alzheimer’s. The major allele variants ApoE3 and ApoE4 differ only by one amino acid. However, this difference has major consequences for the physiological behaviour of each variant. In this paper, we follow i) the initial interaction of lipid-free ApoE variants with model membranes as a function of lipid saturation, ii) the formation of reconstituted High-Density Lipoprotein-like particles (rHDL) and their structural characterisation, and iii) the rHDL ability to exchange lipids with model membranes made of saturated lipids in the presence and absence of cholesterol (DMPC or POPC with and without 20 mol% cholesterol). Our neutron reflection results demonstrate that the protein variants interact differently with the model membranes, adopting different protein conformations. Moreover, the ApoE3 structure at the model membrane is sensitive to the level of lipid unsaturation. Small-angle neutron scattering shows that the ApoE containing lipid particles form elliptical disc-like structures, similar in shape but larger than nascent or discoidal HDL based on Apolipoprotein A1 (ApoA1). Neutron reflection shows that ApoE-rHDL do not remove cholesterol but rather exchange saturated lipids, as occurs in the brain. In contrast, ApoA1-containing particles remove and exchange lipids to a greater extent as occurs elsewhere in the body.